Energy levels, radiative rates and electron impact excitation rates for transitions in Fe xiv. Issue 2 (14th October 2014) - Aggarwal, Kanti M.; Keenan, Francis P.
Abstract : Energies and lifetimes are reported for the lowest 136 levels of Fe xiv, belonging to the (1s 2 2s 2 2p 6 ) 3s 2 3p, 3s3p 2, 3s 2 3d, 3p 3, 3s3p3d, 3p 2 3d, 3s3d 2, 3p3d 2 and 3s 2 4ℓ configurations. Additionally, radiative rates, oscillator strengths and line strengths are calculated for all electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2) and magnetic quadrupole (M2) transitions. Theoretical lifetimes determined from these radiative rates for most levels show satisfactory agreement with earlier calculations, as well as with measurements. Electron impact excitation collision strengths are also calculated with the Dirac atomic R -matrix code (darc ) over a wide energy range up to 260 Ryd. Furthermore, resonances have been resolved in a fine energy mesh to determine effective collision strengths, obtained after integrating the collision strengths over a Maxwellian distribution of electron velocities. Results are listed for all 9180 transitions among the 136 levels over a wide range of electron temperatures, up to 10 7.1 K. Comparisons are made with available results in the literature, and the accuracy of the present data is assessed.